Hubungan antara Faktor Sosiodemografi dan Frekuensi Kunjungan Agroedutourism pada Tanikota - Rosyadilla, Assyifa; Utami, Hesty Nurul (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
One form of business development from the agricultural sector is agroedutourism. Agroedutourism is a combination of agrotourism and edutourism. The increasing need for community recreational tourism encourages agroedutourism to develop further. Apart from that, agroedutourism activities can also be an effort to arouse the interest of the younger generation in agriculture. One of the agroedutourism destination located in Bandung City is Tanikota. However, Tanikota still faces one problem in running its agroeducational tourism program, which is the fluctuating visitors. Apart from marketing factors, we need to know that there are other factors that can influence visits, such as sociodemographic factors. Sociodemographic factors are age, gender, education and income. Therefore, this research wants to know the relationship between sociodemographic factors of Tanikota visitors and the frequency of visiting in Tanikota. Primary data used in this research was obtained from questionnaires distributed online and offline. The number of samples used in this research was 97 people obtained using the Lemeshow formula. The research results in this study were analyzed using descriptive analysis and cross tabulation analysis with Chi-Square calculations. This research found that there was a relationship between age, gender, education and income and the frequency of visits to Tanikota as an agro-tourism location.